TEKNIK SPLIT BOLUS TERHADAP INFORMASI ANATOMIS PADA PEMERIKSAAN CT SCAN UROGRAFI - Amelia Rizqi Utami; Nanang Sulaksono; Sigit Wijokongko (Perhimpunan Radiografer Indonesia (PARI), 2022)
Background : The split bolus technique in CT Scan urography is an intravenous contrast media insertion technique by combining two phases, namely the nephrography phase and the excretory phase in one scan acquisition. In general, the CT Scan urography examination uses 3 phases, non-contrast phase, the nephrographic phase, and the excretory phase. In the role of the split bolus technique, the combination of two phases, namely the nephrographic and excretory phases. The purpose of this study was to explain the split bolus technique and the role of the split bolus technique on anatomical information in CT Scan urography. Methods : This type of descriptive research using a literature review approach. The keywords used are